Diversity and Species Composition of Ants in Urban and Suburban Environments in Bejaia City (Algeria) - Laakel, Nadjet; Aissat, Lyes; Bounab, Leila; Yahiaoui, Cilia (Sociobiology, 2024)
We conducted an ant inventory in urban and suburban spaces in Bejaia city to deal with this need for more information about ant biodiversity in the Algerian urban environment. The two methods, hand collecting and pitfall traps, are carried out 24 days in three months (May, June, and July) of 2022. In the urban habitats, 2,653 ant individuals were collected, comprising ten species, six genera and three subfamilies. In the suburban habitats, 6,706 ant specimens were collected, comprising 19 species, 11 genera, and three subfamilies. The most abundant subfamilies in both urban and suburban habitats are Formicinae, followed by Myrmicinae and Dolichoderinae. The results showed that suburban habitats are more diversified (H’= 1.72) than urban habitats (H’= 1.25). The equitability values for suburban and urban habitats are moderate, with 0.58 and 0.54, respectively. The Jaccard similarity index value is 0.45, indicating an essential turnover of ant species between urban and suburban habitats. The ant community’s composition differed between sampled sites (NMDS, Stress = 0.013). The average dissimilarity (as per SIMPER) was 90.37%. Four species (T. simrothi, L. cf. grandis, P. cicatricosa, and L. myops) contributed to 70% of the differences between sites of urban and suburban habitats.